5 - The Representation of Self Injury and Suicide on Emo Social Networking Groups - Carla Zdanow; Bianca Wright (African Sociological Review, 2013)
The influence of the media on suicide has become a growing topic of discussion in various academic fields. Little attention has however been paid to the influence of social media on teenage suicide. In this age of technological savoir–faire, teenagers are beginning to spend more and more time communicating via internet social networking sites. Recent news reports have blamed both social networking and the teenage emo subculture for romanticising suicide and encouraging and promoting suicidal behaviour online. In these uncensored and unrestrictedonline communities, destructive and dangerous conversations between vulnerable teenagers may go unnoticed. With this in mind, this baseline study aimed to determine the portrayal of suicide and self-harm on social networking sites by analysing the representation of these behaviours among emo teenagers on the popular social networking site Facebook. A content analysis of two emo groups revealed a glorification, normalisation and acceptance of suicidal behaviours and determined that the potential for social networking sites to be used as a tool for the promotion and encouragement of such behaviours exists. As such, with evidence now pointing towards a connection between teenage use of social media and the promotion of positive perceptions of suicidal behaviour, further research into the role of new forms of media in suicide contagion may need to be undertaken.